A lithium-sulfur battery positive electrode and its preparation method and application
By adding N,N'-disalicylic acid copper (II) to the active material layer of the lithium-sulfur battery positive electrode, the problem of polysulfide shuttle effect in the lithium-sulfur battery positive electrode is solved, and the battery performance is improved, especially in terms of discharge efficiency and cycle stability is achieved.
Patent Information
- Application Number
- CN202211406928.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-11-10
AI Technical Summary
The shuttle effect caused by the dissolving of polysulfide in the positive electrode of the lithium-sulfur battery is caused by unstable performance during the charging and discharging process, and the weak van der Waals force between the non-polar host material and the polar polysulfide is difficult to effectively alleviate.
Copper (II) of N,N'-disalicylic acid ethylenediamine is added to the active material layer of the positive electrode of the lithium sulfur battery. This additive relieves the shuttle effect through the chemical adsorption of nitrogen atoms, oxygen atoms and polysulfides, and accelerates the conversion of long-chain polysulfides into short-chain polysulfides through the catalytic performance of copper, thereby improving discharge efficiency.
Effectively inhibit the shuttle of polysulfides and improve the discharge efficiency of lithium-sulfur batteries. The discharge capacity of the first circle can reach more than 1071.61mAh/g, the discharge capacity of the 200 cycle can reach more than 928.21mAh/g, and the efficiency of the 200 cycle can reach more than 96.01%.
Smart Images

Figure CN115528210B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium-sulfur batteries and relates to a lithium-sulfur battery positive electrode and a preparation method and application thereof. Background Art
[0002] Lithium-sulfur batteries, with their high theoretical specific capacity and low price, are considered to be one of the most promising new energy storage devices to meet today's energy and market needs. However, there are still many problems on the road to commercial application of lithium-sulfur batteries.
[0003] CN115053361A discloses a positive electrode for a lithium-sulfur battery and a lithium-sulfur battery comprising the same. The positive electrode for a lithium-sulfur battery comprises a current collector and a positive electrode active material layer arranged on at least one surface of the current collector, wherein the positive electrode active material layer comprises a positive electrode active material and an additive, and the additive comprises a transition metal-ferrocyanide compound.
[0004] CN114141980A discloses a solid-state lithium-sulfur battery positive electrode and an all-solid-state lithium-sulfur battery. The solid-state battery positive electrode comprises a sulfur-containing positive electrode material, a conductive agent, a first binder, a first electrolyte and an additive, wherein the additive comprises a metal element.
[0005] The above scheme has the problems of insulation of sulfur positive electrode materials, volume change during charging and discharging, and shuttle effect caused by polysulfide dissolving in electrolyte. Most research on lithium-sulfur battery positive electrode focuses on non-polar conductive carbon materials. However, the weak van der Waals force between non-polar host materials and polar polysulfides cannot effectively alleviate the shuttle effect. Summary of the invention
[0006] The purpose of the present invention is to provide a lithium-sulfur battery positive electrode and a preparation method and application thereof. The present invention can effectively inhibit the shuttling of polysulfides by adding N,N′-disalicylicylaldehyde ethylenediamine copper (II) to the lithium-sulfur battery positive electrode, catalytically accelerate the conversion of long-chain polysulfides into short-chain polysulfides, and accelerate the discharge process.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a lithium-sulfur battery positive electrode, which comprises a positive electrode collector and an active material layer arranged on the surface of the positive electrode collector, wherein the active material layer comprises a sulfur-carbon composite positive electrode material, a conductive agent, a binder and N,N′-disalicylicaldehyde ethylenediamine copper (II).
[0009] The present invention adds N,N'-disalicylicaldehyde ethylenediamine copper (II) as an additive in the positive electrode active material layer of the lithium-sulfur battery. The chemical adsorption of nitrogen atoms and oxygen atoms existing in the N,N'-disalicylicaldehyde ethylenediamine copper (II) itself and polysulfides alleviates the shuttle effect caused by the polysulfides dissolving in the electrolyte in the positive electrode of the lithium-sulfur battery. At the same time, the catalytic performance of copper in the N,N'-disalicylicaldehyde ethylenediamine copper (II) molecules accelerates the conversion of long-chain polysulfides into short-chain polysulfides, thereby accelerating the discharge process.
[0010] Preferably, the positive electrode current collector comprises carbon-coated aluminum foil.
[0011] Preferably, the conductive agent comprises conductive carbon black.
[0012] Preferably, the binder comprises polyvinylidene fluoride.
[0013] Preferably, the mass ratio of the sulfur-carbon composite positive electrode material to N,N′-disalicylicaldehyde ethylenediamine copper (II) is (6-8):(0.1-2), for example: 6:2, 7:1, 6.5:1.5, 7.2:0.5 or 7.9:0.1, etc.
[0014] Preferably, the sulfur-carbon composite positive electrode material loading of the lithium-sulfur battery positive electrode is 1.0-1.5 mg / cm 2 , for example: 1.0mg / cm 2 , 1.1mg / cm 2 , 1.2mg / cm 2 , 1.3mg / cm 2 , 1.4mg / cm 2 or 1.5 mg / cm 2 wait.
[0015] In a second aspect, the present invention provides a lithium-sulfur battery positive electrode as described in the first aspect, wherein the preparation method comprises the following steps:
[0016] (1) mixing sublimated sulfur and a carbon source, adding CS2, sealing and stirring, volatilizing the solvent, and drying to obtain a sulfur-carbon composite positive electrode material;
[0017] (2) The sulfur-carbon composite positive electrode material, the conductive agent, the binder and N,N′-disalicylicaldehyde ethylenediamine copper (II) are mixed and ground, and then a solvent is added to obtain a positive electrode slurry. The positive electrode slurry is coated on the surface of the positive electrode current collector, and dried to obtain the lithium-sulfur battery positive electrode.
[0018] Preferably, the carbon source in step (1) comprises conductive carbon black.
[0019] Preferably, the mass ratio of the sublimated sulfur to the carbon source is (6-8):(4-2), for example: 6:4, 6.5:3.5, 7:3, 7.2:2.5 or 8:2, etc.
[0020] Preferably, the sealed stirring time is 20 to 30 hours, for example, 20 hours, 22 hours, 25 hours, 28 hours or 30 hours.
[0021] Preferably, the sample is ground before drying.
[0022] Preferably, the grinding time is 0.8 to 1.2 h, for example, 0.8 h, 0.9 h, 1 h, 1.1 h or 1.2 h.
[0023] Preferably, the drying temperature is 55-65°C, for example, 55°C, 58°C, 60°C, 62°C or 65°C.
[0024] Preferably, the drying time is 10 to 15 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.
[0025] Preferably, the mixing and grinding time in step (2) is 30 to 60 min, for example, 30 min, 35 min, 40 min, 50 min or 60 min.
[0026] Preferably, the solvent comprises N-methylpyrrolidone.
[0027] Preferably, the positive electrode slurry is stirred into a paste state.
[0028] Preferably, the thickness of the coating scraper in step (2) is 200-300 μm, for example, 200 μm, 220 μm, 250 μm, 280 μm or 300 μm.
[0029] Preferably, the drying process includes air drying followed by vacuum drying.
[0030] Preferably, the temperature of the forced air drying is 40-50°C, for example, 40°C, 42°C, 45°C, 48°C or 50°C.
[0031] Preferably, the vacuum drying temperature is 55-65°C, for example, 55°C, 58°C, 60°C, 62°C or 65°C.
[0032] Preferably, the vacuum drying time is 10 to 15 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.
[0033] In a third aspect, the present invention provides a lithium-sulfur battery, wherein the lithium-sulfur battery comprises the lithium-sulfur battery positive electrode as described in the first aspect.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The present invention can effectively inhibit the shuttling of polysulfides by adding N,N′-disalicylicaldehyde ethylenediamine copper (II) to the positive electrode of the lithium-sulfur battery, catalytically accelerate the conversion of long-chain polysulfides into short-chain polysulfides, and speed up the discharge process.
[0036] (2) The lithium-sulfur battery positive electrode of the present invention has a first-cycle discharge capacity of more than 1071.61 mAh / g, a 200-cycle discharge capacity of more than 928.21 mAh / g, and a 200-cycle coulomb efficiency of more than 96.01%. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a charge and discharge curve of a battery made from the positive electrode of the lithium-sulfur battery described in Example 1 at 25° C. and 0.5C.
[0038] Figure 2 The discharge capacity and coulomb efficiency curve of the battery made of the lithium-sulfur battery positive electrode described in Example 1 after 200 cycles. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] Example 1
[0041] This embodiment provides a lithium-sulfur battery positive electrode, and the lithium-sulfur battery positive electrode is prepared by the following method:
[0042] (1) Using the impregnation method, 700 mg of sublimated sulfur and 300 mg of conductive carbon black were weighed into a 25 mL weighing bottle, CS2 was added until the powder sample was just submerged, the sample was tightly sealed and placed in a fume hood with magnetic stirring for 24 h, the lid was opened and the solvent was completely evaporated, the sample was taken out, ground for 1 h, and placed in a vacuum oven at 60 ° C for 12 h to obtain a sulfur-carbon composite positive electrode material;
[0043] (2) Weigh the sulfur-carbon composite positive electrode material, conductive carbon black, polyvinylidene fluoride, and N,N′-disalicylicaldehyde ethylenediamine copper (II) in a mass ratio of 7:1:1:1, grind in a mortar for 40 minutes, transfer to a 5 mL weighing bottle, add an appropriate amount of NMP solution, and stir at room temperature for 3 hours to mix into a uniform paste. Use a scraper to evenly coat the obtained electrode material slurry on the carbon-coated aluminum foil with a scraper thickness of 250 μm, put it in a 45°C forced air drying oven for drying, and then vacuum dry it at 60°C for 12 hours. After taking it out, cut it into discs on a punching machine, press it into discs, and weigh it. The mass of the sulfur-carbon composite positive electrode material loaded on the electrode is about 1.2 mg / cm 2 .
[0044] The charge and discharge curve of the lithium-sulfur battery positive electrode at 25°C and 0.5C is as follows Figure 1 As shown, the discharge capacity and coulomb efficiency curve of the lithium-sulfur battery positive electrode made into a battery after 200 cycles is as shown in Figure 2 shown.
[0045] Example 2
[0046] This embodiment provides a lithium-sulfur battery positive electrode, and the lithium-sulfur battery positive electrode is prepared by the following method:
[0047] (1) Using the impregnation method, 700 mg of sublimated sulfur and 300 mg of conductive carbon black were weighed into a 25 mL weighing bottle, CS2 was added until the powder sample was just submerged, the sample was tightly sealed and placed in a fume hood with magnetic stirring for 24 h, the lid was opened and the solvent was completely evaporated, the sample was taken out, ground for 1 h, and placed in a vacuum oven at 60 ° C for 12 h to obtain a sulfur-carbon composite positive electrode material;
[0048] (2) Weigh the sulfur-carbon composite positive electrode material, conductive carbon black, polyvinylidene fluoride, and N,N′-disalicylicaldehyde ethylenediamine copper (II) in a mass ratio of 6.5:1:1:1.5, grind in a mortar for 40 minutes, transfer to a 5 mL weighing bottle, add an appropriate amount of NMP solution, and stir at room temperature for 3 hours to mix into a uniform paste. Use a scraper to evenly coat the obtained electrode material slurry on the carbon-coated aluminum foil with a scraper thickness of 250 μm, put it in a 45°C forced air drying oven for drying, and then vacuum dry it at 60°C for 12 hours. After taking it out, cut it into discs on a punching machine, press it, and weigh it. The mass of the sulfur-carbon composite positive electrode material loaded on the electrode is about 1.2 mg / cm 2 .
[0049] Example 3
[0050] This embodiment provides a lithium-sulfur battery positive electrode, and the lithium-sulfur battery positive electrode is prepared by the following method:
[0051] (1) Using the impregnation method, 700 mg of sublimated sulfur and 300 mg of conductive carbon black were weighed into a 25 mL weighing bottle, CS2 was added until the powder sample was just submerged, the sample was tightly sealed and placed in a fume hood with magnetic stirring for 24 h, the lid was opened and the solvent was completely evaporated, the sample was taken out, ground for 1 h, and placed in a vacuum oven at 60 ° C for 12 h to obtain a sulfur-carbon composite positive electrode material;
[0052] (2) Weigh the sulfur-carbon composite positive electrode material, conductive carbon black, polyvinylidene fluoride, and N,N′-disalicylicaldehyde ethylenediamine copper (II) in a mass ratio of 7.5:1:1:0.5, grind in a mortar for 40 minutes, transfer to a 5 mL weighing bottle, add an appropriate amount of NMP solution, and stir at room temperature for 3 hours to mix into a uniform paste. Use a scraper to evenly coat the obtained electrode material slurry on the carbon-coated aluminum foil with a scraper thickness of 250 μm, put it in a 45°C forced air drying oven for drying, and then vacuum dry it at 60°C for 12 hours. After taking it out, cut it into discs on a punching machine, press it, and weigh it. The mass of the sulfur-carbon composite positive electrode material loaded on the electrode is about 1.2 mg / cm 2 .
[0053] Example 4
[0054] This embodiment provides a lithium-sulfur battery positive electrode, and the lithium-sulfur battery positive electrode is prepared by the following method:
[0055] (1) Using the impregnation method, 700 mg of sublimated sulfur and 300 mg of conductive carbon black were weighed into a 25 mL weighing bottle, CS2 was added until the powder sample was just submerged, the sample was tightly sealed and placed in a fume hood with magnetic stirring for 24 h, the lid was opened and the solvent was completely evaporated, the sample was taken out, ground for 1 h, and placed in a vacuum oven at 60 ° C for 12 h to obtain a sulfur-carbon composite positive electrode material;
[0056] (2) Weigh sulfur-carbon composite positive electrode material, conductive carbon black, polyvinylidene fluoride, N,N′-disalicylicaldehyde ethylenediamine copper (II) in a mass ratio of 5.5:1:1:2.5, grind in a mortar for 40 minutes, transfer to a 5 mL weighing bottle, add an appropriate amount of NMP solution, and stir at room temperature for 3 hours to mix into a uniform paste. Use a scraper to evenly coat the obtained electrode material slurry on the carbon-coated aluminum foil with a scraper thickness of 250 μm, put it in a 45°C forced air drying oven for drying, and then vacuum dry it at 60°C for 12 hours. After taking it out, cut it into discs on a punching machine, press it into discs, and weigh it. The mass of active material loaded on the electrode is about 1.2 mg / cm 2 .
[0057] Comparative Example 1
[0058] This embodiment provides a lithium-sulfur battery positive electrode, and the lithium-sulfur battery positive electrode is prepared by the following method:
[0059] (1) Using the impregnation method, 700 mg of sublimated sulfur and 300 mg of conductive carbon black were weighed into a 25 mL weighing bottle, CS2 was added until the powder sample was just submerged, the sample was tightly sealed and placed in a fume hood with magnetic stirring for 24 h, the lid was opened and the solvent was completely evaporated, the sample was taken out, ground for 1 h, and placed in a vacuum oven at 60 ° C for 12 h to obtain a sulfur-carbon composite positive electrode material;
[0060] (2) Weigh the sulfur-carbon composite positive electrode material, conductive carbon black, polyvinylidene fluoride, and N,N′-disalicylicaldehyde ethylenediamine copper (II) in a mass ratio of 8:1:1:0, grind in a mortar for 40 minutes, transfer to a 5 mL weighing bottle, add an appropriate amount of NMP solution, and stir at room temperature for 3 hours to mix into a uniform paste. Use a scraper to evenly coat the obtained electrode material slurry on the carbon-coated aluminum foil with a scraper thickness of 250 μm, put it in a 45°C forced air drying oven for drying, and then vacuum dry it at 60°C for 12 hours. After taking it out, cut it into discs on a punching machine, press it into discs, and weigh it. The mass of the sulfur-carbon composite positive electrode material loaded on the electrode is about 1.2 mg / cm 2 .
[0061] Performance Testing:
[0062] Take the lithium-sulfur battery positive electrode obtained in Examples 1-4 and Comparative Example 1, use LiTFSI and EC / DEC (v / v, 1 / 1) to configure 1 mol / L electrolyte, use a CR2032 button cell, and the battery assembly is carried out in a glove box filled with argon gas. The concentration of water and oxygen in the glove box is strictly controlled below 1ppm. First, place the negative electrode shell on a flat table, put in the spring sheet, gasket, and metal lithium sheet (specification of Φ16.8×0.4mm) in turn and place them in the middle position, then put on the diaphragm, then drop 50μL of electrolyte, place the positive electrode sheet in the middle, and finally cover the positive electrode shell, buckle it, and package it on a hydraulic packaging machine. Take it out to complete the assembly of the entire battery, let it stand overnight, and test its electrochemical performance at a constant temperature of 25°C. The test results are shown in Table 1:
[0063] Table 1
[0064]
[0065] As can be seen from Table 1, from Examples 1-3, the first cycle discharge capacity of the battery prepared by the lithium-sulfur battery positive electrode of the present invention can reach more than 1071.61 mAh / g, the discharge capacity after 200 cycles can reach more than 928.21 mAh / g, and the coulombic efficiency after the 200th cycle can reach more than 96.01%.
[0066] By comparing Example 1 and Example 4, it can be seen that in the positive electrode of the lithium-sulfur battery of the present invention, the addition amount of N,N′-disalicylicaldehyde ethylenediamine copper (II) needs to be controlled within a certain range. If the mass proportion of N,N′-disalicylicaldehyde ethylenediamine copper (II) in the positive electrode active material layer exceeds 20%, it will affect the proportion of the positive electrode active material. The more additives, the lower the content of the positive electrode active material, which will affect the long-term cycle capacity of the battery.
[0067] By comparing Example 1 with Comparative Example 1, it can be seen that in the present invention, N,N′-disalicylicylaldehyde ethylenediamine copper (II) is added as an additive in the positive electrode active material layer of the lithium-sulfur battery, and the chemical adsorption of nitrogen atoms and oxygen atoms existing in N,N′-disalicylicylaldehyde ethylenediamine copper (II) itself and polysulfides alleviates the shuttle effect caused by the dissolution of polysulfides in the electrolyte in the positive electrode of the lithium-sulfur battery.
[0068] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A lithium-sulfur battery positive electrode, characterized in that: The lithium-sulfur battery positive electrode comprises a positive electrode current collector and an active material layer disposed on the surface of the positive electrode current collector, wherein the active material layer comprises a sulfur-carbon composite positive electrode material, a conductive agent, a binder and N,N′-disalicylicaldehyde ethylenediamine copper (II); The mass percentage of the N,N′-disalicylicylethylenediamine copper (II) in the active material layer is less than 20%.
2. The lithium-sulfur battery positive electrode according to claim 1, characterized in that The positive electrode current collector includes carbon-coated aluminum foil.
3. The lithium-sulfur battery positive electrode according to claim 1, characterized in that The conductive agent includes conductive carbon black.
4. The lithium-sulfur battery positive electrode according to claim 1, characterized in that The binder includes polyvinylidene fluoride.
5. The lithium-sulfur battery positive electrode according to claim 1, characterized in that The mass ratio of the sulfur-carbon composite positive electrode material to N,N′-disalicylicylethylenediamine copper (II) is (6-8):(0.1-2).
6. The lithium-sulfur battery positive electrode according to claim 1, characterized in that The sulfur-carbon composite positive electrode material loading of the lithium-sulfur battery positive electrode is 1.0-1.5 mg / cm 2 .
7. A method for preparing a positive electrode for a lithium-sulfur battery as claimed in any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing sublimated sulfur and a carbon source, adding CS2, sealing and stirring, volatilizing the solvent, and drying to obtain a sulfur-carbon composite positive electrode material; (2) The sulfur-carbon composite positive electrode material, the conductive agent, the binder and N,N′-disalicylicaldehyde ethylenediamine copper (II) are mixed and ground, and then a solvent is added to obtain a positive electrode slurry. The positive electrode slurry is coated on the surface of the positive electrode current collector, and dried to obtain the lithium-sulfur battery positive electrode.
8. The preparation method according to claim 7, characterized in that: The carbon source in step (1) includes conductive carbon black.
9. The preparation method according to claim 7, characterized in that: The mass ratio of the sublimated sulfur to the carbon source is (6-8):(4-2).
10. The preparation method according to claim 7, characterized in that: The sealing and stirring time is 20 to 30 hours.
11. The preparation method according to claim 7, characterized in that: The sample is ground before the drying.
12. The preparation method according to claim 11, characterized in that: The grinding time is 0.8 to 1.2 hours.
13. The preparation method according to claim 7, characterized in that: The drying temperature is 55-65°C.
14. The preparation method according to claim 7, characterized in that: The drying time is 10 to 15 hours.
15. The preparation method according to claim 7, characterized in that: The mixing and grinding time in step (2) is 30 to 60 minutes.
16. The preparation method according to claim 7, characterized in that: The solvent included N-methylpyrrolidone.
17. The preparation method according to claim 7, characterized in that: The positive electrode slurry is stirred into a paste state.
18. The preparation method according to claim 7, characterized in that: The thickness of the coating scraper in step (2) is 700 to 800 μm.
19. The preparation method according to claim 7, characterized in that: The drying process includes air-blast drying followed by vacuum drying.
20. The preparation method according to claim 19, characterized in that: The temperature of the blast drying is 40-50°C.
21. The preparation method according to claim 19, characterized in that: The vacuum drying temperature is 55-65°C.
22. The preparation method according to claim 19, characterized in that: The vacuum drying time is 10 to 15 hours.
23. A lithium-sulfur battery, characterized in that: The lithium-sulfur battery comprises the lithium-sulfur battery positive electrode according to any one of claims 1 to 6.
Citation Information
Patent Citations
Method of producing porous metal-carbon materials
CN107073440A
Polymer-modified electrode for energy storage devices and electrochemical supercapacitor based on said polymer-modified electrode
US20040057191A1